Phasor Estimation Techniques with a Focus on Wide Area Measurement System - Rohini Haridas (International Journal of Advanced Science and Technology, 2020)
Power system is coming further complex because of development of transmission and distribution network, competitive electricity market, widespread use of power electronics devices etc. Under such difficulties, the requirement for uninterrupted and smooth automated control of power flows wants new real-time measurement methods for smart grids. At the moment, the state of the power system is typically observed through the so-called wide-area monitoring systems (WAMS). The PMUs are the crucial elements of the WAMS, as they execute the phasor estimation of various waveforms over an extensive area at the same time. Thus the accurate estimation of synchronized phasors in phasor measurement units is noteworthy in power system, monitoring, protection, and control. Synchro phasor estimation methods have been of great concern for the last two years both in academia and the power system practitioners world. This paper provides a broad review of different synchrophasor estimation methods which are commonly used for wide-area measurement system.Keywords: Phasor ; Phasor estimation ; synchrophasor ; PMU; wide area measurement system; synchrophasor standard